2012
DOI: 10.1111/j.1600-0714.2012.01203.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of carcinogenic acetaldehyde by Candida albicans from patients with potentially malignant oral mucosal disorders

Abstract: Candida albicans isolated from potentially carcinogenic oral diseases can produce mutagenic amounts of acetaldehyde. Cigarette smoking and alcohol consumption may favour adaptational changes resulting in the upregulation of candidal acetaldehyde metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 42 publications
1
69
2
2
Order By: Relevance
“…Many studies have suggested that the production of carcinogenic acetaldehyde by Candida contributes to epithelial dysplasia, and some of them have shown that Candida albicans isolated from potentially malignant disorders can produce carcinogenic substances [27][28][29]. Because this study also showed that the antifungal drug had a positive effect on 3 lesions, we indicated the probable presence of antifungals effective against leukoplakia.…”
Section: Discussionmentioning
confidence: 75%
“…Many studies have suggested that the production of carcinogenic acetaldehyde by Candida contributes to epithelial dysplasia, and some of them have shown that Candida albicans isolated from potentially malignant disorders can produce carcinogenic substances [27][28][29]. Because this study also showed that the antifungal drug had a positive effect on 3 lesions, we indicated the probable presence of antifungals effective against leukoplakia.…”
Section: Discussionmentioning
confidence: 75%
“…[20] Candida albicans isolated from potentially malignant disorders may also produce mutagenic amounts of acetaldehyde. [24] Further, a biological injection phenomenon has been proposed by which hyphae may serve as tracts through which carcinogens travel deep into the epithelium even though Candida affects only the superficial layers initially. [25] Barring one patient, all the patients in our study smoked, chewed tobacco and/or used alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…(42) Oral bacterial flora including Nesseria and Streptococcus and Candida metabolize ethanol to acetaldehyde through an activity of alcohol dehydrogenase (ADH). (4345) Acetaldehyde in saliva is considered carcinogenic substance. (43) Drinking and smoking are also known to shift the balance of bacterial flora, resulting in an increment of acetaldehyde in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%